Isothermal crystallization behavior of lard at different temperatures studied by DSC and real-time XRD. (March 2015) - Steen, Liselot; Rigolle, Annelien; Glorieux, Seline; Paelinck, Hubert; Fraeye, Ilse; Goderis, Bart; Foubert, Imogen
Abstract: Differential scanning calorimetry and real-time X-ray diffraction using synchrotron radiation were used to study the isothermal crystallization formation mechanism of lard at 18, 20, 22 and 24 °C. At 18 °C, lard crystallized in three steps. A potential mechanism for these three steps was proposed. In the first step, part of the melt (the trisaturated triacylglycerols (TAGs)) crystallized in α crystals adopting a double length structure (2L), while the second step consisted of a polymorphic transition of these 2Lα crystals to β′ crystals with a triple length structure (3L). Extra 3Lβ′ crystals consisting of monounsaturated TAGs were also formed directly from the melt. In the third and last step, β crystals were formed due to a second polymorphic transition of trisaturated 3Lβ′ crystals to β crystals adopting a 2L structure. Above a cut-off temperature of 20 °C lard crystallized in two steps: no formation of α crystals could be observed and 3Lβ′ crystals (trisaturated and monounsaturated TAGs) were formed directly from the melt. This proposed mechanism implies that lard crystallization is characterized by an overlap of fractionated crystallization and polymorphic transitions. Highlights: Lard is characterized by fractionated crystallization and polymorphic transitions. 18 °C: lard is a three-step crystallization process with α crystals in the 1st step. Above a temperature of 20 °C lard crystallized in two steps with no α crystals.